Phytoplankton phenology in the coastal upwelling region off central‐southern Chile (35°S–38°S): Time‐space variability, coupling to environmental factors, and sources of uncertainty in the estimates. Issue 2 (12th February 2015) - Corredor‐Acosta, Andrea; Morales, Carmen E.; Hormazabal, Samuel; Andrade, Isabel; Correa‐Ramirez, Marco A.
Abstract The annual cycle and phenology of phytoplankton (satellite‐derived chlorophyll‐a, Chl‐a) in the coastal upwelling region off central‐southern Chile, their time‐space variation, the extent of their coupling with those of wind‐driven upwelling (as Zonal Ekman Transport, ZET), Sea Surface Temperature (SST), and Photosynthetically Active Radiation (PAR) were analyzed using a ∼10 year satellite time series (2002–2012). Wavelet analysis (WA) was applied to extract the dominant frequencies of variability and their recurrence, to derive the phenological indexes, and to assess the extent of the coupling between Chl‐a and environmental forcing in the annual frequency. Index estimates were obtained from minimum and maximum accumulated values in two different frequency bands, annual (WA‐ANF) and all except the synoptic (WA‐ALF). The annual frequency was dominant in all the variables; however, the annual cycle and phenology of Chl‐a displayed higher submeso and mesoscale variability. The mean onset date of Chl‐a was similar to those of PAR and ZET with WA‐ALF and cross WA indicated that, for the most part, their annual cycles were coupled or coherent. Few interannual changes in Chl‐a phenology were detected, including a ∼1 month longer duration (WA‐ALF) during La Niña 2010–2011. The mean anomalies in the magnitudes of Chl‐a and ZET during the upwelling season showed a slight but significant trend, negative for Chl‐a and positive for ZET, while SST remained relatively constant. This pattern was unexpected since three La Niña‐related conditions were identified during the 2007–2012 period.